Diverging Discourses on Bauxite Mining in Eastern India: Life-Supporting Hills for Adivasis or National Treasure Chests on Barren Lands?. Issue 8 (3rd August 2017) - Oskarsson, Patrik
ABSTRACT: This article identifies the two dominant discourses that attempt to explain socioenvironmental change from bauxite mining in Eastern India and compares them to empirical material from three proposed mining locations. The anti-mining "life-giving hills" discourse understands the bauxite-bearing hills as an essential part of a wider ecosystem that supports sustainable, indigenous communities. The pro-mining "treasure chest" discourse, on the other hand, sees barren, uninhabited hilltops with rich ore deposits possible to extract for the benefit of the nation without harming nearby forests or communities. It is found that both discourses hold universalizing aspirations not backed up by available evidence. The technical rationality of mining proponents create sweeping generalizations resulting in unmitigated socio-environmental change, while the eco-romanticist opposition fails to see how communities and environments are differentially affected by mining. Two untenable discourses at present underpin seemingly intractable conflict without addressing wider resource politics dominated by political and business elites.